Decidual macrophages in recurrent spontaneous abortion - Zhao, Qiu-Yan; Li, Qing-Hui; Fu, Yao-Yao; Ren, Chun-E; Jiang, Ai-Fang; Meng, Yu-Han (Frontiers in Immunology, 2022)
Recurrent spontaneous abortion (RSA) is defined as two or more pregnancy loss, affecting the happiness index of fertility couples. The mechanisms involved in the occurrence of RSA are not clear to date. The primary problem for the maternal immune system is how to establish and maintain the immune tolerance to the semi-allogeneic fetuses. During the pregnancy, decidual macrophages mainly play an important role in the immunologic dialogue. The purpose of this study is to explore decidual macrophages, and to understand whether there is a connection between these cells and RSA by analyzing their phenotypes and functions. Pubmed, Web of Science and Embase were searched. The eligibility criterion for this review was evaluating the literature about the pregnancy and macrophages. Any disagreement between the authors was resolved upon discussion and if required by the judgment of the corresponding author. we summarized the latest views on the phenotype, function and dysfunction of decidual macrophages to illuminate its relationship with RSA.